Sikkim Draft Annual Plan 1995-96 (Volume-II) - Planning Commission (Planning Commission, 1994)
Progress of Expenditure 1994-95 and Proposed Outlay 1995-96 Physical targets and achievements 1994-95 and Proposals for 1995-96 Proposals for spillover and ongoing programmes and projects Proposals for maximising benefits of completed programmes/projects Proposals for programmes/projects -New schemes of plan Summary Statement Statement regarding externally aided project Outlay for District Plan 1995.
Planning and Development Department, Government of Sikkim